Técnicas de enseñanza y su incidencia en el proceso de aprendizaje de los estudiantes con autismo de la Unidad Educativa Emigdio Esparza Moreno de la ciudad de Babahoyo, 2022 – 2023 - Sánchez González, Miguel Ángel (2023)
Teaching techniques refer to the specific strategies and methods that educators use to transmit information, facilitate learning and promote understanding. These techniques allow us to respond to the needs of students with ASD and create inclusive and active classes. For this reason, the main objective of this research is to determine the impact of teaching techniques on the learning process of students with autism at the “Emigdio Esparza Moreno” Educational Unit in the city of Babahoyo, 2022 – 2023. The methodology used in the case study conforms to a qualitative approach; While the research was descriptive, field and explanatory, inductive and deductive methods were also used, the population and sample are represented by 2 students with autism and the tutor teacher of the 5th year of EGB, parallel "D", is also considered to the educational psychologist, belonging to the “Emigdio Esparza Moreno” Educational Unit, it is important to mention that to obtain relevant information on the topic, two techniques were used: direct observation, aimed at autistic students, an interview with the teacher was also used. and the psychologist. The results obtained were that in the 5th year EGB parallel "D" of the Emigdio Esparza Moreno Educational Unit, the teaching techniques is not efficient, the creativity and skills of the teacher are not demonstrated to help students with ASD to conceive. Knowledge in a constructivist way.